syclone- design-geometric developing a computer program to design cyclones: environmental pollution (Journal of Hama University, 2024)
Laboratories and factories emit many particles, gases, dust, smoke, fume and vapors that pollute the air, which negatively affect humans, animals, and plants. Methods for treating air pollution vary according to the type of pollutants and their physical conditions.Toxic pollutants need specific treatment, but most industrial facilities release dust, smoke, fume and coarse particles, in addition to other pollutants. Cyclones are considered as one of the most important inertial separation devices and are widely used for gathering coarse particulate matters with medium size, because the simplicity of their spread and the relative low cost, make them used as primary cleaners for other more expensive devices. Cyclones have different types (High Efficiency-Conventional- High Throughput) are usually designed with geometric similarity so that the ratios between the dimensions are fixed and related to diameter of the cyclone body D. In this work, a computer program Cyclone was designed using Visual Basic programming language, so that we can design the cyclone various types of Cyclones depending on standard ratios of their geometries By using the program, the cyclone can be designed by knowing its diameter D or knowing length of the entrance, will be possible to draw the designed cyclone with calculated dimensions.We can also know the number of cycles of vortices (Ne). After giving different values for D and H it was found that the value of (Ne) for one type of cyclone remains constant with the change of the diameter or the length of the inlet:The results: - For High Efficiency and Conventional Cyclones ( Ne= 5-6 steps). -For High Throughput Cyclones (Ne= 3-4 steps).Suggestions: Cyclones are not sufficient alone in many cases. Therefore, other facilities must be designed as filtrations, absorption devices, adsorption devices. Pollutants must also be controlled as much as possible by reducing pollutants before they leave the source. Pollution, and awareness and health education should be more considered in the field of environmental pollution
Keywords: Syclone App- Design- geometric